Deformation modes and crashworthiness energy absorption of sinusoidally corrugated tubes manufactured by direct metal laser sintering. (15th December 2019) - Alkhatib, Sami E.; Matar, Mohammad S.; Tarlochan, Faris; Laban, Othman; Mohamed, Ahmed S.; Alqwasmi, Nouman
Graphical abstract: Highlights: Sinusoidally corrugated tubes were additively manufactured through DMLS. A sample of 8 tubes were heat treated and crushed experimentally under quasi-static tests. The crushing and energy absorption behavior of the tubes were studied. Abstract: Thin-walled structures are used for crashworthiness energy absorption applications such as automobile vehciles and aircraft. Structures of sinusoidally corrugated profiles were of great interest because of their ability to reduce the peak crushing forces and provide stable energy-absorbing patterns. Studies on structures of sinusoidally corrugated profiles are limited to numerical studies due to manufacturing limitations. Advancement in additive manufacturing enables the fabrication of structures of complex profiles such as corrugated tubes. This could solve the issue of mass productions of such structures for energy absorption applications. This paper aims to additively manufacture and test sinusoidally corrugated tubes experimentally. A sample of 8 sinusoidally corrugated tubes was additively manufactured and tested under a quasi-static displacement rate of 20 mm/min. The results showed that corrugated tubes exhibit lower and stable crushing forces compared to conventional straight tubes. It was found that increasing the wavelength from 10 to 20 mm results in changing deformation mode from ring to diamond, while increasing the amplitude from 1 to 2 mm has no effect when the thickness is 1 mm. Corrugated tubes achieved a maximum peak force reduction of 75%, and a maximum crushing force efficiency increase of 63%. However, they also resulted in a reduction of 46 and 55% in energy absorption and specific energy absorption, respectively.